Exploration of The Kizkumu Legend Through The Lens of Party Dress With Automatic Method - Ardani, Wanda Marshia; Wiana, Winwin; Astuti, Astuti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The demand for designers’ creative exploration of ideas aligns with the challenges of transforming traditional fashion into contemporary designs. To achieve this, it is crucial to strike a balance between preserving tradition and embracing modernity. Therefore, the primary objective of this research is to gather data on how to utilize oral tradition, particularly the Legend of Kizkumu, as a source of inspiration for creating party dresses using the ATUMICS method. The ATUMICS method serves as a guiding framework to systematically organize the source of ideas for each design element, encompassing both the micro and macro levels. These levels include artifacts, techniques, utilities, materials, icons, concepts, and shapes. The research culminates in the creation of a party dress inspired by the Kizkumu Legend, which retains its traditional elements such as icons, concepts, shapes, and utilities. The design process commenced with brainstorming sessions to identify the unique aspects of the Kizkumu legend related to Kizkumu beach and its symbolic representation as a statue. This exploration culminated in the realization of a party dress that encapsulates the essence of the Kizkumu Legend through each design element.